CD38 expression in early B‐cell precursors contributes to extracellular signal‐regulated kinase‐mediated apoptosis. Issue 2 (February 2015) - Romero‐Ramírez, Héctor; Morales‐Guadarrama, Monserrat Teresa; Pelayo, Rosana; López‐Santiago, Rubén; Santos‐Argumedo, Leopoldo
Summary CD38 is a 45 000 molecular weight transmembrane protein that is expressed in immature and mature lymphocytes. However, the expression and function of CD38 during B‐cell differentiation in mice is poorly understood. Here, we report that CD38 is expressed from the earliest stages of B‐cell development. Pre‐pro‐B, pro‐B, pre‐B and immature B cells from murine bone marrow all stained positive for CD38. Interestingly, CD38 expression increases with B‐cell maturation. To assess the role of CD38 during B‐cell maturation, CD38‐deficient mice were analysed. CD38−/− mice showed a significant increase in both the frequency of B‐lineage cells and the absolute numbers of pre‐pro‐B cells in bone marrow; however, no other differences were observed at later stages. CD38 cross‐linking in Ba/F3 cells promoted apoptosis and marked extracellular signal‐regulated kinase (ERK) phosphorylation, and these effects were reduced by treatment with the mitogen‐activated protein kinase/ERK kinase inhibitor PD98059, and similar effects were observed in B‐cell precursors from bone marrow. These data demonstrate that B‐cell precursors in mouse bone marrow express functional CD38 and implicate the early ligation of CD38 in the ERK‐associated regulation of the B‐lineage differentiation pathway.